2018
DOI: 10.1002/advs.201800736
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Lithium Doping in Reducing Nonradiative Loss in Lead Halide Perovskites

Abstract: Adding alkali metal into lead halide perovskites has recently been demonstrated as an effective strategy for reducing nonradiative loss. However, the suggested role of the alkali metal is usually limited to surface passivation, and the semiconductor doping effect is rarely discussed. Here, the mechanism of lithium doping in the photocarrier recombination in solution‐processed methylammonium lead halide films is investigated by photoluminescence and photoelectron spectroscopies. It is demonstrated that lithium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 48 publications
7
43
1
Order By: Relevance
“…Typically, A 1 and A 2 are the relative amplitudes, B is offset value, τ 1 represents the information for the interface recombination process, and τ 2 reflects the information for the bulk recombination process . The average lifetime τ avg has also been calculated to determine the whole recombination process, as given by Equation : trueτnormalanormalvnormalg=Aiτi/Ai …”
Section: Resultsmentioning
confidence: 99%
“…Typically, A 1 and A 2 are the relative amplitudes, B is offset value, τ 1 represents the information for the interface recombination process, and τ 2 reflects the information for the bulk recombination process . The average lifetime τ avg has also been calculated to determine the whole recombination process, as given by Equation : trueτnormalanormalvnormalg=Aiτi/Ai …”
Section: Resultsmentioning
confidence: 99%
“…Fang et al. have observed that lithium can enter the lattice of MAPbI 3 and induce n‐type doping, creating free electrons to fill the trap states such as interstitial iodine, and suppressing nonradiative recombination . Son et al.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Fang et al have observed that lithium can enter the lattice of MAPbI 3 and induce n-type doping, creating free electrons to fill the trap states such as interstitial iodine,and suppressing nonradiative recombination. [23] Son et al have investigated the role of potassium in passivating defects,reporting that potassium can be easily mixed into FA 0.85 MA 0.1 Cs 0.05 PbI 2.7 Br 0.3 and impede formation of interstitial iodine and other iodine-related Frenkel defects. [24] Thei ntroduction of potassium removes the current-voltage hysteresis,a nd reduces lowfrequency capacitance and trap density.A bdi-Jalebi et al have successfully controlled the nonradiative losses and photoinduced ion migration in perovskite films and interfaces by decorating surfaces and grain boundaries with potassium halide layers.…”
Section: Introductionmentioning
confidence: 99%
“…This PL trend with lithium doping can be understood from reduced trapping. 20 In the absence of lithium dopants, unfilled trap states are present, potentially due to grain boundaries, vacancies, and other imperfections that create nonradiative decay states in the middle of the optical gap. These trap states must first be filled with electronic carriers before steady PL can be achieved.…”
mentioning
confidence: 99%